2014
DOI: 10.2217/nnm.14.109
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterials: The Next Step in Injectable Bone Cements

Abstract: Injectable bone cements (IBCs) are biocompatible materials that can be used as bone defect fillers in maxillofacial surgeries and in orthopedic fracture treatment in order to augment weakened bone due to osteoporosis. Current clinically available IBCs, such as polymethylmethacrylate and calcium phosphate cement, have certain advantages; however, they possess several drawbacks that prevent them from gaining universal acceptance. New gel-based injectable materials have also been developed, but these are too mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 129 publications
(212 reference statements)
0
44
0
Order By: Relevance
“…During surgery, bone cement is formed into a paste by mixing the powder and the liquid, and the paste can then either be injected through a channel or molded by the surgeon into the sites of bone defects or voids. 39 After setting and hardening, the paste conforms to the shape of the defect or void, and solidifies to achieve enough strength to support the vertebra. The characteristics and properties of PMMA, CPC, and CSC for vertebroplasty and kyphoplasty are shown in Table 2.…”
Section: Bone Cementsmentioning
confidence: 99%
See 4 more Smart Citations
“…During surgery, bone cement is formed into a paste by mixing the powder and the liquid, and the paste can then either be injected through a channel or molded by the surgeon into the sites of bone defects or voids. 39 After setting and hardening, the paste conforms to the shape of the defect or void, and solidifies to achieve enough strength to support the vertebra. The characteristics and properties of PMMA, CPC, and CSC for vertebroplasty and kyphoplasty are shown in Table 2.…”
Section: Bone Cementsmentioning
confidence: 99%
“…55 Although adding nanofibers has a positive effect by enhancing the mechanical properties of CPC, identification of suitable nanofibers that are bioresorbable and bioactive while being able to provide sufficient strength and fracture toughness remains challenging. 39 Recent studies have demonstrated that carbon nanotubes (CNTs) may be a reasonable choice. In the study by Wang et al, incorporation of 0.2 wt% and 0.5 wt% as-received CNTs into CPC resulted in an increase in compressive strength by 24%, and biomineralized CNTs led to a 120% increase in the compressive strength of CPC.…”
Section: Calcium Phosphate Cementmentioning
confidence: 99%
See 3 more Smart Citations